Working With School-Age Children, Part 1: Preventing Misbehavior - Millie Ferrer; Anne Fugate; Ingrid Rivera (EDIS, 2002)
This document is FCS2200, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication: July 2002.